Comparison of Surface Area across the Allograft-Host Junction Site Using Conventional and Navigated Osteotomy Technique. (18th December 2012) - Lall, Ajay; Hohn, Eric; Kim, Mimi Y.; Gorlick, Richard G.; Abraham, John A.; Geller, David S.
Abstract : Bulk allograft reconstruction plays an important role in limb-salvage surgery; however, non-union has been reported in up to 27% of cases. The purpose of this study is to quantify average surface contact areas across simulated intraoperative osteotomies using both free-hand and computer-assisted navigation techniques. Pressure-sensitive paper was positioned between two cut ends of a validated composite sawbone and compression was applied using an eight-hole large fragment dynamic compression plate. Thirty-two samples were analyzed for surface area contact to determine osteotomy congruity. Mean contact area using the free-hand osteotomy technique was equal to 0.21 square inches. Compared with a control of 0.69 square inches, average contact area was found to be 30.5% of optimal surface contact. Mean contact area using computer-assisted navigation was equal to 0.33 square inches. Compared with a control of 0.76 square inches, average contact area was found to be 43.7% of optimal surface contact. Limited contact achieved using standard techniques may play a role in the high rate of observed non-union, and an increase in contact area using computer-assisted navigation may improve rates of bone healing. The development of an oncology software package and navigation hardware may serve an important role in decreasing non-union rates in limb salvage surgery.